Early Evaluation of the Fetal Heart - Edgar Hernandez-Andrade (2018)
© 2017 S. Karger AG, Basel. Copyright: All rights reserved. Evaluation of the fetal heart at 11-13 + 6 weeks of gestation is indicated for women with a family history of congenital heart defects (CHD), a previous child with CDH, or an ultrasound finding associated with cardiac anomalies. The accuracy for early detection of CHD is highly related to the experience of the operator. The 4-chamber view and outflow tracts are the most important planes for identification of an abnormal heart, and can be obtained in the majority of fetuses from 11 weeks of gestation onward. Transvaginal ultrasound is the preferred route for fetal cardiac examination prior to 12 weeks of gestation, whereas, after 12 weeks, the fetal heart can be reliably evaluated by transabdominal ultrasound. Cardiac defects, such as ventricular septal defects, tetralogy of Fallot, Ebstein's anomaly, or cardiac tumors, are unlikely to be identified at ≤14 weeks of gestation. Additional ultrasound techniques such as spatiotemporal image correlation and the evaluation of volumes by a fetal-heart expert can improve the detection of congenital heart disease. The evaluation of the fetal cardiac function at 11-13 + 6 weeks of gestation can be useful for early identification of fetuses at risk of anemia due to hemoglobinopathies, such as hemoglobin Bart's disease.